Pengaruh Backward Walking Exercise Terhadap Nyeri Dan Kemampuan Fungsional Pasien Osteoarhtritis Genu - Khumaerah, Aulia; Yusfina, Yusfina; Tenriola, Andi (UI Scholars Hub, 2023)
Osteoarthritis (OA) is a degenerative disease that mainly attacks the joints and surrounding tissues, causing progressive damage to cartilage, subchondral bone and synovial structures. Genu OA is the most common OA and can cause disabilities that interfere with daily activities, reduce quality of life and increase the risk of falls. Physiotherapy intervention for genu OA can be conducted using various methods, one of them is backward walking exercise. The study is a quasi experimental research using two group pre and post-test control group design. The aim of the research is to determine the effect of backward walking exercise on pain and functional ability in patients with genu OA. The pain scale was measured using the Visual Analog Scale (VAS) and the patient's functional ability was measured using the Physical Function using Western Ontario and McMaster Universities Arthritis Index (WOMAC). The samples were all patients who had been diagnosed with Genu OA and met the predetermined inclusion and exclusion criteria. The samples were divided into 2 groups, the intervention group and the control group. Each group will receive the same physiotherapy intervention, but the intervention group was given additional intervention in the form of backward walking exercises. Backward walking exercise was conducted 2 times a week for 4 weeks. Before administering the exercise, each patient measured their pain scale and functional capacity. The measurement was done again after 8 interventions. The results showed that patients in the intervention group experienced a significant increase in functional ability (p=0.003) and a significant reduction in pain (p=0.000). In the control group there was also a significant increase in functional ability (p=0.000) and pain reduction (p=0.000). However, there was no significant difference in results between the control group and the intervention group in terms of functional ability (p=0.135) and pain level (p=0.490)